Early life influences on child weight outcomes in the Study to Explore Early Development. (May 2019) - Kral, Tanja VE; Chittams, Jesse; Bradley, Chyrise B; Daniels, Julie L; DiGuiseppi, Carolyn G; Johnson, Susan L; Pandey, Juhi; Pinto-Martin, Jennifer A; Rahai, Neloufar; Ramirez, AnnJosette; Schieve, Laura A; Thompson, Aleda; et al.
We examined associations between child body mass index at 2–5 years and maternal pre-pregnancy body mass index, gestational weight gain, and rapid weight gain during infancy in children with autism spectrum disorder, developmental delays, or population controls. The Study to Explore Early Development is a multi-site case–control study of children, aged 2–5 years, classified as autism spectrum disorder ( n  = 668), developmental delays ( n  = 914), or population controls ( n  = 884). Maternal gestational weight gain was compared to the Institute of Medicine recommendations. Rapid weight gain was a change in weight-for-age z -scores from birth to 6 months > 0.67 standard deviations. After adjusting for case status, mothers with pre-pregnancy overweight/obesity were 2.38 times (95% confidence interval: 1.96–2.90) more likely, and mothers who exceeded gestational weight gain recommendations were 1.48 times (95% confidence interval: 1.17–1.87) more likely, to have an overweight/obese child than other mothers ( P  < 0.001). Children with autism spectrum disorder showed the highest frequency of rapid weight gain (44%) and were 3.47 times (95% confidence interval: 1.85–6.51) more likely to be overweight/obese as children with autism spectrum disorder without rapid weight gain ( P  < 0.001). Helping mothers achieve a healthy pre-pregnancy body mass index and gestational weight gain represent important targets for all children. Healthy infant growth patterns carry special importance for children at increased risk for an autism spectrum disorder diagnosis.